2018
DOI: 10.1016/j.shaw.2017.08.005
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Prevalence and Risk Factors for Varicose Veins in Nurses at a University Hospital

Abstract: BackgroundLower-limb varicose veins (VVs) are common and known to have a higher prevalence among people who work in occupations requiring prolonged standing. In the Republic of Korea, however, VV-related occupational factors have seldom been examined. This study was conducted to assess the prevalence of VVs among nurses, an occupational group considered to be at high risk of VVs, and determine the occupational risk factors of prolonged standing.MethodsBetween March and August 2014, a questionnaire survey coupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
54
5
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 27 publications
(37 reference statements)
9
54
5
7
Order By: Relevance
“…In contrast, the prevalence in the present study was higher than that in a study performed with nurses working at a university hospital in Pusan, republic of Korea, in which 16.5% of the women suffered from varicose veins. (11) However, a much higher prevalence (78%) of varicose veins was found in another study among female nurses in the general hospital in Amol, Iran.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In contrast, the prevalence in the present study was higher than that in a study performed with nurses working at a university hospital in Pusan, republic of Korea, in which 16.5% of the women suffered from varicose veins. (11) However, a much higher prevalence (78%) of varicose veins was found in another study among female nurses in the general hospital in Amol, Iran.…”
Section: Discussionmentioning
confidence: 87%
“…(13,20) Other studies found eczema, skin trophic changes and lipodermatosclerosis, and these skin conditions are usually complications due to late diagnosis of chronic venous insufficiency and ulceration, making a cure difficult. (15,18,19) As a result of these findings, it is important to discover varicose veins early before complications occur; therefore, screening and in Korea, who used compression stockings for prevention and treatment purposes (11) , while illiterate women (94.4%) than among nonworkers and educated women. This finding may be due to the fact that workers are exposed to long period of standing, which is considered a risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…The primary cause of the disease and its consequences is the lack of prevention due to insufficient knowledge about the risk factors, which primarily include age, the female gender, positive family history, congenital anomalies of the veins, pregnancy, obesity, constipation, hormonal changes, high ambient temperature as well as long stay in a sitting or standing position and is related to the work performed [5,6]. A significant relationship between postures adopted at work and the development and/or exacerbation of chronic venous insufficiency symptoms has been the subject of many scientific studies [7][8][9][10]. These works usually concerned the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…Male predominance with 66.25% of males in our study was observed which is similar to the findings of many Indian studies, but studies conducted in western countries report female dominance which is due to the scenario that females in india are not exposed to high risk of work which involve prolonged standing and physical stress due to cultural and socioeconomic conditions. 4 In the present study, majority of the cases (40%) were in the age group of 41 to 50 years with a mean age of 43.40 years which is on par with the findings in the study of Mishra et al from india and McGuckin et al 5,6 As most of the studies universally reported, dilated veins was the most common symptom in our study also with 85% of cases as compared to Rudofsky et al with 90% and Shankar et al with 94% in their studies. 7,8 Observation of varicose veins in several members of the same family suggest a clear hereditary factor as cause of varicose veins, in our study 30% of the cases had a definitive family history which is similar to the reports of Staniszewska et al who conducted a study among the European population and reported significant association between varicose veins and family history.…”
Section: Discussionmentioning
confidence: 99%